DIPLOMA PROJECT DESIGN AND WAYS OF ITS IMPLEMENTATION (FROM THE PRACTICE OF THE DIPLOMA HEAD) (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the issues of preparation and implementation diploma students. The effectiveness of pedagogical activity in point of realization of individuality in the creative embodiment of the idea diploma work. The process of professional growth of a teacher is studied fine arts in higher education.
Keywords: deep realization; individuality; creative idea; formation of skills of independent research and creative work